Global perspective on marital satisfaction - Dobrowolska, Małgorzata (2020)
Across the world, millions of couples get married each year. One of the strongest predictors of whether partners will remain in their relationship is their reported satisfaction. Marital satisfaction is commonly found to be a key predictor of both individual and relational well-being. Despite its importance in predicting relationship longevity, there are relatively few empirical research studies examining predictors of marital satisfaction outside of a Western context. To address this gap in the literature and complete the existing knowledge about global predictors of marital satisfaction, we used an open-access database of self-reported assessments of self-reported marital satisfaction with data from 7178 participants representing 33 different countries. The results showed that sex, age, religiosity, economic status, education, and cultural values were related, to various extents, to marital satisfaction across cultures. However, marriage duration, number of children, and gross domestic product (GDP) were not found to be predictors of marital satisfaction for countries represented in this sample. While 96% of the variance of marital satisfaction was attributed to individual factors, only 4% was associated with countries. Together, the results show that individual differences have a larger influence on marital satisfaction compared to the country of origin. Findings are discussed in terms of the advantages of conducting studies on large cross-cultural samples